Adverse childhood experiences screening in pediatric primary care and changes in the rate of visits to social work and behavioral health - Sonya Negriff; Margo Sidell; Lee Barton; Mercie J. DiGangi (BMC Pediatrics)
Abstract Background There is increasing interest in screening for adverse childhood experiences in pediatric primary care, but no evidence of the actual consequences on behavioral/mental health services. This study tested the association between initiation of ACEs screening in pediatric primary care and changes in the rate of referrals to social work and visits to social work and behavioral health. Methods Data came from the electronic health records of children and adolescents between 2 and 18 years old who were members of a large integrated healthcare system serving Southern California (N = 513,812). Poisson regression was used to compare the rate of referrals and visits to social work and behavioral health visits for clinics doing standardized ACEs screening (i.e., intervention clinics; n = 28) versus clinics not screening (i.e., control clinics; n = 64) during June 1-December 31 2022 as well as for these same months in 2020 and 2021. Results Intervention clinics had an average screening rate of 57% (range 26.8 to 91.9%) and an average positive screen rate of 11% (range 1.6–25.1%). The difference in the adjusted rate from 2021 to 2022 was significantly different between intervention and control clinics for referrals to social work (RR 1.48, 95% CI 1.25, 1.74), but was not statistically different for visits to social work or behavioral health. Conclusions The findings suggest that ACEs screening does not significantly increase the rates of social work and behavioral health visits, although it did increase referrals to social work. We acknowledge that this may vary based on geographic areas and populations served by different healthcare systems.